Respiratory tract involvement in primary Sjögren’s syndrome, focus on interstitial lung disease - B. D. Chaltsev; V. I. Vasilyev; I. O. Avetisov; A. V. Torgashina; E. V. Sokol; Yu. I. Khvan; L. P. Ananyeva (Научно-практическая ревматология, 2022)
The article provides a literature review on the current understanding of respiratory tract damage in primary Sjögren’s syndrome (pSS) with an emphasis on interstitial lung disease (ILD), as well as approaches to the differential diagnosis, treatment, and screening of pSS-ILD.